Intention-based reciprocity and the hidden costs of control - Ferdinand von Siemens (Center for Economic Studies and ifo Institute (CESifo), 2011)
Empirical research suggests that - rather than improving incentives - exerting control can reduce workers' performance by eroding motivation. The present paper shows that intention-based reciprocity can cause such motivational crowding-out if individuals differ in their propensity for reciprocity and preferences are private information. Not being controlled might then be considered to be kind, because not everybody reciprocates not being controlled with high effort. This argument stands in contrast to existing theoretical wisdom on motivational crowding-out that is primarily based on signaling models.
Keywords: A13; C70; D63; D82; L20; 330; extrinsic and intrinsic motivation; crowding-out; intention-based reciprocity; incomplete information; hidden costs of control; Leistungsmotivation; Leistungsbeurteilung; Austauschtheorie (Soziologie); Crowding out; Asymmetrische Information; Theorie